Manejo clínico de un paciente con estomatitis aftosa recurrente aplicando laser terapéutico Beatríz Guzmán de Suárez, Arnulfo Arias Rojas - Guzmán de Suárez, Beatriz; Arias Rojas, Arnulfo (Revista Estomatología, 1993)
The recurrent aftosa estomatic is a sore sickness. This has bad a big controversy because of its name, origen and treatment. As a contribution we show the conduct ofthe oral wound faced to the therapeutical las ser as one alternative of treatment and we take into account that this phisycal agent doesn’t produce colateral effects. It is of easy aplication with analgesic activity and it’ not inflammatory and it acelerates the healing process.